THE IMPLEMENTATION OF FAIR VALUE ON SHORT TERM ASSESMENT OF BIOLOGICAL ASSETS - Murtianingsih, Murtianingsih; Setiawan, Anas Hari (Journal of Accounting and Business Education, 2016)
This study aims to identify and analyze the implementation of fair value and the impact of the use of bases the recognition, measurement, and disclosure of the biological assets with the object of research PT. Malindo Feedmill Tbk which further research is also useful for agriculture companies in managerial decision making. This research is descriptive quantitative concluded based on data and clarify the picture of the implementation of fair value is based on International Accounting Standard (IAS) 41 and perform comparative measurements of biological assets PT. Malindo Feedmill, Tbk based acquisition price. From the results of this study concluded that the difference in the material due to fair value measurement that refers to IAS 41 in determining the market value following the fluctuations of the market, but in IAS 41 does not distinguish between fair value treatment against several categories of biological assets. This is certainly less relevant when applied to some types of biological assets, such as short term biological assets at PT. Malindo Feedmill Tbk.Keywords: biological assets, fair value, historical cost, ias 41